The impact of self-monitoring physical and mental health via an mHealth application on postpartum weight retention: Data from the INTER-ACT RCT - Femke Geusens; Hanne Van Uytsel; Lieveke Ameye; Roland Devlieger; Yves Jacquemyn; Caroline Van Holsbeke; Annick Bogaerts (Tabriz University of Medical Sciences, 2024)
Background: Postpartum weight retention (PPWR) has many health risks. Digital self-monitoring of weight can potentially make postpartum weight management easier. We aim to test to what extent the self-monitoring of weight, steps and mental health through an mHealth application increases postpartum weight loss and reduces the odds of substantial PPWR (≥5 kg). Methods: Participants were mothers in the intervention arm of the INTER-ACT multicenter randomized controlled trial (RCT), an inter-pregnancy lifestyle intervention among mothers with excessive gestational weight gain. Participants (n=288) had access to an mHealth application to log their weight, steps and mental health between 6 weeks and 6 months postpartum. A linear multiple regression model and a logistic regression model were run to test to what extent self-monitoring via the app increases postpartum weight loss and reduces the risk of substantial PPWR. Results: Women who logged their weight more often lost more weight (B=0.03, β=0.26, CIB =[0.01,0 .05], P<0.01), and had reduced odds of substantive PPWR (OR=0.99, CIOR =[0.98, 0.999], P<.05). Mental health logging reduced the odds of substantive PPWR (OR=0.98, CIOR =[0.97, 1.00], P<0.05), but was unrelated to the amount of weight loss. Steps logging was unrelated to either weight loss or substantive PPWR. Conclusion: Mothers with excessive gestational weight gain can benefit from app-based lifestyle interventions to reduce PPWR by self-monitoring their weight. More attention to mental health in PPWR interventions is needed.